Post-dynamic α to β phase transformation and reverse transformation of Ti-5Al-3V alloy after hot deformation in two phase region. (March 2020) - Ji, Xiankun; Yu, Hong; Guo, Baoqi; Jiang, Fulin; Fu, Dingfa; Teng, Jie; Zhang, Hui; Jonas, John J.
Abstract: The microstructural evolutions and resulted mechanical responses during isothermal holding of multipass hot deformation are essential aspects in the processing of high performance titanium alloys. In this work, isothermal holding testing was performed on a Ti-5Al-3V alloy after hot compression at temperatures of 900 °C, 930 °C and 960 °C, respectively. Stress relaxation, dilatometer measurements, and microstructure examinations (i.e. scanning electron microscope, electron backscatter diffraction and transmission electron microscope) were employed to investigate the phase transformation behaviors. The results showed a flow stress hardening phenomenon during the interrupted isothermal holding in two phase region. The post-dynamic transformation from α to β phase took place first during the early stage of isothermal holding after hot deformation. With longer isothermal holding time, the reverse transformation of meta-stable β phase to α phase was then observed. Under TEM, the reverse transformed α phases were isolated from quenched α ' phases. The in-depth mechanisms of post-dynamic α to β phase transformation and reverse transformation were discussed as well. Graphical abstract: Unlabelled Image Highlights: Flow stress hardening is found during double-stage deformation in two phase region. A post-dynamic transformation of α to β phase occurred during interrupted holding. The reverse transformation of β phase to α phase occurred with further holding. The reverse transformed α phases were distinguished from α ' phases by TEM. The post-dynamic transformation should be driven by stored energy and stress.